The Portuguese observatory on occupational psychosocial factors: contribution for public health: Claudia Fernandes. (25th October 2022) - Fernandes, C; Cotrim, T; Pereira, A; Silva, CF; Bem-Haja, P; Azevedo, R; Antunes, S; Pinto, J Sousa; Silva, I
Abstract:  : To achieve the goal of sustainable employment, considering the profile of the Portuguese working population (PWP), is needed a range of strategies to ensure long, productive, and sustainable careers allied with a better quality of working life, health, and wellbeing, but also with public health policies grounded on scientifically validated and reliable data. This is possible through a comprehensive working system approach that ensures workers will be mentally and physically able to remain at work by the balance between work demands and individual resources allied with public health policies transfer into the workplaces by organizations' leadership and policy makers. The Portuguese Observatory on Occupational Factors (Popsy@Work ) aims at addressing this global challenge by: i) digitally collecting psychosocial data on the PWP; ii) implementing and strengthening of a psychosocial occupational health surveillance digital system; iii) providing reference values for the PWP concerning Psychosocial Health; iv) Transferring to society knowledge and best practices; v) Raising awareness on the importance of psychosocial management in occupational settings based on science. Popsy@work is a digital platform that collects and aggregates psychosocial data analytically and creates a visualization hub adding value to data on the PWP and giving science back to society in a usable way, empowering workers, strengthening organizations and grounding public policies. Pospy@Work considers the development of strategic intelligence on levels and inequalities of psychosocial health and well-being in occupational settings by robust metrics and reference data. Creating opportunities for national policy dialogue on inequalities, including the psychosocial health of the PWP through collaboration with diverse sectors identifying and mapping subgroups of populations whose unmet needs require specific outreach measures. Key messages: Popsy@work allows psychosocial health monitoring, reporting and foresight, promoting the provision of robust metrics and reference values for the Portuguese working population. Popsy@work allows psychosocial health on occupational settings to be digitally monitored in a continuous way and sustain public health policies.